Personal Hygiene Skills are Not Related to Infections in School-Age Children - Maria Anita Yusiana; Sandy Kurniajati; Erva Elli Kristanti; Dyah Ayu Kartika Wulan Sari (Babali Publisher, 2022)
Introduction: The incidence of infection in school-age children can be caused by the negligence of children in carrying out personal hygiene, namely washing hands and due to contact with individuals who have been infected with pathogens. Infectious diseases that often suffer are upper respiratory infection, diarrhea, and intestinal worms with symptoms of fever. Preventive efforts that can be done by children are personal hygiene (washing hands). Prevention of infection in children is done by teaching school-age children to wash their hands properly. The objective of this study was to analyze personal hygiene skills (hand washing) with the incidence of infection in children. Methods: The method in this study was a pre-experimental study with a pretest-posttest design. The samples were 20 respondents of school-age children. Differences in pretest-posttest personal hygiene skills (hand washing). Results: The results are based on data collected from 20 subjects, the results of the pretest-posttest personal hygiene skills (hand washing) in the Wilcoxon test, there was a significant difference, namely (p = 0.541). Conclusion: There was no correlation between personal hygiene (hand washing) and the incidence of infection.